2020
DOI: 10.1186/s12883-019-1586-x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood neurodegeneration associated with a specific UBTF variant: a new case report and review of the literature

Abstract: Background: A new monogenic neurodegenerative disease affecting ribosomal metabolism has recently been identified in association with a monoallelic UBTF putative gain of function variant (NM_001076683.1:c.628G>A, hg19). Phenotype is consistent among these probands with progressive motor, cognitive, and behavioural regression in early to middle childhood. Case presentation: We report on a child with this monoallelic UBTF variant who presented with progressive disease including regression, episodes of subacute d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…A variant of UBTF encoding another transcription factor of Pol I (UBF) has recently been associated with neurodegenerative disease in children 3‐6 . The main clinical features were highly similar to the phenotype of the patients in this study (Table 1).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A variant of UBTF encoding another transcription factor of Pol I (UBF) has recently been associated with neurodegenerative disease in children 3‐6 . The main clinical features were highly similar to the phenotype of the patients in this study (Table 1).…”
Section: Discussionsupporting
confidence: 68%
“…A variant of UBTF encoding another transcription factor of Pol I (UBF) has recently been associated with neurodegenerative disease in children. [3][4][5][6] The main clinical features were highly similar to the phenotype of the patients in this study (Table 1). After being initially normal, brain MRI of Patient 1 showed white matter hyperintensities in T2-weighted images, thinning of the corpus callosum, and diffuse brain atrophy ( Figure 2) which have also been reported with the UBTF variant.…”
Section: Molecular Genetic Studiessupporting
confidence: 54%
See 1 more Smart Citation
“…An E>K mutation at residue 210 in HMGbox2 of Ubtf was recently shown to be the cause of a recurrent human pediatric neuroregression syndrome (6,(11)(12)(13). The key role of HMGbox2 revealed by our study suggested that this mutation might affect the formation of the RPI preinitiation complex in vivo and possibly explain the origin of this syndrome.…”
Section: An Hmgbox2 Mutation Linked To Neuroregression Potentially Affects Ubtf Interactionsmentioning
confidence: 54%
“…Here we show that despite having little or no inherent DNA sequence selectivity, the multi-HMGbox Upstream Binding Factor (UBF/UBTF) plays a crucial role in targeting RPI preinitiation complex formation to the rDNA promoters in vivo. Further, we show that this UBTF function is compromised by an E210K mutation recently linked to a recurrent human pediatric neuroregression syndrome (6,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 67%